The evaluation of oral health knowledge in secondary school students in Lublin - Szyszkowska, Anna; Mazurek, Mateusz (Polish Journal of Public Health, 2012)
Introduction. The pressure put on young people to achieve good results in many disciplines of life should also include encouraging them to keep oral hygiene perfect. Unfortunately, results of Polish research show that the condition of teeth and gingiva of Polish teenagers according to different indicators is still unsatisfying. Aim. The purpose of the study was to determine the level of oral hygiene knowledge in secondary students in Lublin. Material and methods. The study included 682 students, aged 16-18, attending secondary schools in Lublin. The patients answered questions regarding reasons for their visit to the dental practice, and for not seeing a dental practitioner on a regular basis. They also covered selected hygiene practices. Results. The results showed that in the surveyed group 17% of students went to see the dentist less often than once a year; 19% changed their toothbrushes not more often than once every 3 months and 38% of the students were afraid of the dentist. One or more teeth were lostby 14% of the surveyed students because of dental caries. Surprisingly every fifth surveyed student did not know how many teeth an adult should have. Conclusions. On the basis of the results of the conducted study, it has been concluded that the secondary school students have a low level of oral hygiene knowledge, which is reflected in an insufficient motivation to appropriately follow daily preventive dentistry and avoiding seeing the dentist for check-ups.